2003
DOI: 10.1074/jbc.m307976200
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of the 3′ Splice Site by U2AF65

Abstract: Recognition of the 3 splice site in mammalian introns is accomplished by association of the splicing factor U2AF with the precursor mRNA (pre-mRNA) in a multiprotein splicing commitment complex. It is well established that this interaction involves binding of the large U2AF65 subunit to sequences upstream of the 3 splice site, but the orientation of the four domains of this protein with respect to the RNA and hence their role in structuring the commitment complex remain unclear and the basis of contradictory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
40
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 36 publications
(61 reference statements)
6
40
0
Order By: Relevance
“…Another example is stabilizing interactions mediated by arginineserine-rich (RS) domains, which support protein-protein interactions as well as interactions between proteins harboring these domains and double-stranded RNA regions (e.g., those resulting from base pairing between U2 snRNA and the branch site region) (Wu and Maniatis 1993;Green 2004 2006;. Furthermore, the arrangement of protein and RNA contacts in the initial complex has been proposed to enforce a unique RNA structure in the 39 splice site that may be critical to trigger subsequent events in the splicing process (Kent et al 2003). In addition, proofreading activities exist that ensure proper assembly of splicing factors in bona fide splice site signals, e.g., allowing the assembly of U2AF on uridine-rich sequences only if followed by a 39 splice site AG dinucleotide (Soares et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is stabilizing interactions mediated by arginineserine-rich (RS) domains, which support protein-protein interactions as well as interactions between proteins harboring these domains and double-stranded RNA regions (e.g., those resulting from base pairing between U2 snRNA and the branch site region) (Wu and Maniatis 1993;Green 2004 2006;. Furthermore, the arrangement of protein and RNA contacts in the initial complex has been proposed to enforce a unique RNA structure in the 39 splice site that may be critical to trigger subsequent events in the splicing process (Kent et al 2003). In addition, proofreading activities exist that ensure proper assembly of splicing factors in bona fide splice site signals, e.g., allowing the assembly of U2AF on uridine-rich sequences only if followed by a 39 splice site AG dinucleotide (Soares et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…U2AF65 binds specifically to the Py tract via its C-terminal RNA-binding domain, which consists of three RNA recognition motifs (RRMs) (Ruskin et al 1988;Zamore et al 1992; for review, see Krämer 1996). U2AF65 stabilizes the interaction of U2 snRNP with the BP by contacting the branch region through its N-terminal arginine-and serine-rich (RS) domain, promoting base pair interactions between U2 snRNA and the BP (Lee et al 1993;Gaur et al 1995;Valcarcel et al 1996;Kent et al 2003). In previous models it was suggested that U2AF65 function is based on interactions between RRM3 and SF1/ mBBP, or the U2 snRNP component SAP155, respectively (Berglund et al 1997;Gozani et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…LS additionally cooperates with the branch point adenosine-binding SF1 through interactions in its C-terminal pseudo-RNA recognition motif (RRM) (Kent et al 2003;Selenko et al 2003). Following these contacts, the 39 end of the intron is then competent for interaction with U2 snRNP.…”
mentioning
confidence: 99%